Evaluating Changes in Perceived Enjoyment throughout a 12-Week School-Based Exergaming Intervention - Lisa Röglin; Oliver Stoll; Kerstin Ketelhut; Anna Lisa Martin-Niedecken; Sascha Ketelhut (MDPI AG, 2023)
This study assessed whether a high-intensity exergame represents an enjoyable training tool for children in the elementary school setting. Furthermore, it evaluated whether gender, body mass index (BMI), waist-to-height ratio (WHtR), fitness level, weekly physical activity level, and general interest in sports moderate perceived enjoyment during the 12-week intervention. Thirty fifth- and sixth-grade students (10.5 ± 0.7 years; 50% girls) participated in this study. During baseline assessments, anthropometric measurements and a shuttle run test were conducted. Throughout the intervention period, the students participated in 15-20-min exergaming sessions (ES) in the ExerCube twice a week during school hours. Enjoyment was assessed after an ES in weeks 2 and 12. Additionally, enjoyment was evaluated after a physical education (PE) class in week 2. The results reveal no significant changes in enjoyment (p = 0.164) over time. The modest changes over time were significantly affected by BMI (p = 0.027), WHtR (p = 0.007), and weekly activity level (p = 0.016). Compared to the PE class, enjoyment was significantly higher during the ES (p < 0.001). None of the covariates showed a significant effect. Mean HR during the ES reached 87.1 ± 1.9% of students' individual maximum HR. In conclusion, the ExerCube provides a promising tool for schools to promote enjoyable moderate-to-vigorous physical activity.